The effect of nutrition education on balanced-nutrition knowledge and macronutrient intake among adolescent - Mardiana Mardiana; Yulianto Yulianto (Intelektual Pustaka Media Utama, 2022)
Counseling on balanced nutrition is unknown among the wider community, especially school students. Therefore, it is necessary to socialize the delivery of messages and principles regarding balanced nutrition. The study analyzed comics and booklets on increasing knowledge level of nutrition and macronutrient intake in adolescents. The study employed a quasi-experimental design, which pre-test and post-test intervention compared to control. The sample of this study was junior high school students selected based on the inclusion and exclusion criteria. The respondent in this study was 150 students of junior high school in Palembang, Indonesia. Paired t-test and ANOVA test as well as regression correlation were used as statistical analysis. The results showed differences in knowledge of the balanced nutrition and macronutrient intake after comic intervention compared to booklets and no intervention.